Uso potencial das terras no município de Catalão (GO) - Silva, Antonio Santiago da (2018)
This study aims at producing a potential land use map in Catalão (GO) according to its physical and natural characteristics, as well as the characterization of the physical environment through the compilation of thematic maps of geology, of geomorphology, of soils, of drainage networks for the production of sub-basin maps, hypsometry, land slope, land use and native vegetation cover of 2016, based on the information collected in field and in documentary sources. The organization and analysis of the data extracted from the thematic maps helped in the production and the proposition of a map of the appropriate use of the land of the municipality, according to its physical-natural characteristics. Thus, in the operational procedures, the methodology for geographic research was used in four levels (or stages): the compiler, the correlation, the semantic and the normative. The images used to carry out this work were image 1: 100.000 from IBGE and OLI / Landsat8 images, ALOS PALSAR, among others. In the QGIS software and algorithm, modules there were vector maps of slope, hypsometry, land use capacity and potential land use. The lithology has 11 classes, the Araxá - A (NPaa) Group is constituted of Amphibolite, Chlorite schist, Muscovite - biotite schist, Ferruginous quartzite, Graphite shale, Talc schist, Hornblende gnaisse, Metacalcary, Muscovite quartzite. In the mapping, it was found that the class (NPaa) occurs in 35.43% and represents the highest percentage of the municipality. The relief has a homogeneous tabular dissection with poorly dissected relief (45.56%), the class with the largest area. In relation to the altitude, this varies between 520 and 960m, there is a predominance of 720 to 840m, equivalent to 36.33%. The predominant slope range is 3% to 8%, with smooth undulating relief occurring in 42.19% of Catalan. The soils of the municipality, in general, are acid and the class with the highest occurrence is the Oxisols in 43.62%, followed by Cambisols with 23.41% of the total area. The mapping of categories of land use and vegetation coverage has 11 classes, it was verified that the class of native vegetation cover occupies 35.13% of area, while the pasture occupy 27.65% the highest percentage of anthropic intervention followed by agricultural areas with 26.80%, of the total area of use of the Municipality. In the municipality of Catalão, the cultivated pasture class occupies 13.33%, followed by the agricultural culture class (8.43%) and the Silviculture class (Pinus, Eucalyptus or Rubber) with 1.86% and other smaller ones, adding 24.6% of anthropic APP areas. The lands classified in the map land use capacity showed that classes I, II and III, equivalent to 69.85% of the research area are suitable for agriculture, but protecting those in areas of permanent preservation. Class IV lands represent 3.64% of the total area, with limitations that are even more severe for crops. Class VI land with 13.12% of the area is recommended for pasture and reforestation. Class VII indicated for reforestation accounts for 2.83% of the total area. The lands of class VIII indicated for the fauna and flora with 5.34%. Eventually, the potential land use map which was elaborated considered the potential of natural resources, the fragilities of natural environmental systems and the recovery of degraded environments. Potential land use classes in the municipality of Catalão show that of the total land recommended, 40.69% is for agriculture, 11.84% for pasture, 3.32% for reforestation and 38.33% for preservation.